Percepcja szans sukcesu sportowego i jej psychologiczne implikacje dla kobiet i mezczyzn - Mroczkowska, H. (Medycyna sportowa, 2001)
As follows from studies on the motivational goal perspective, women appear to be stronger motivated than men by the ego-task orientation (self-perfection). The latter are predominantly driven by the personal orientation (winning in a competition). However, that view is not reflected in the perceived sport capacities of women. Irrespectively of the exhibited motivational tendency, men display a more positive self-image than women. The aim of the study has been to find out whether the subjective assessment of odds for success overcomes gender-related differences in the perceived predispositions for sports and in the dominating type of orientation (task vs. personal). Male (n = 41) and female (n = 29) fencers (mean age 18 years, mean athletic experience 6 years) were studied with use of questionnaire technique. The perceived sport predispositions and odds for a future success were measured by Likert- and Thurstone-types of scales, and the motivational task-ego orientation by the Perceived Competence scale. In general, higher perceived odds for success are associated with a stronger task orientation and higher perceived sport predispositions, irrespectively of gender. However, women feel a high chance for success considerably less frequently than men: only about 25% of women have such feelings, and about 20% of women rate their chances for success as low. The latter ones exhibit a pronounced motivational personal orientation and low perceived sport predispositions, which is an unfavourable prognosis of a long lasting sport career. The attitude to see own capacities in relation to those of contestants, confronted with a reduced self-esteem and poor perspectives of success, induces in those women the feeling of a failed self-accomplishment and of non-fulfillment.